Indirect protection from rotavirus vaccines: a systematic review - Tyler Chavers; Jordan Cates; Eleanor Burnett; Umesh D. Parashar; Jacqueline E. Tate (Expert Review of Vaccines, 2024)
Introduction Rotavirus vaccines may provide indirect protection by reducing transmission in the population and thus reducing disease burden.Methods This systematic review summarizes estimates of indirect protection from rotavirus vaccines and the methods used to obtain these estimates.Results We identified 71 studies published between 2009 and 2022 that provided 399 estimates of indirect protection from rotavirus vaccine. Most estimates (73%) evaluated hospitalizations due to rotavirus gastroenteritis as the outcome and unvaccinated children <5 years old as the agegroup (64%), but there was considerable variability in methods to evaluate indirect protection. For hospitalizations due to rotavirus gastroenteritis among unvaccinated children <5 years old, the median incidence rate ratio was 0.60 (IQR: 0.40–0.87, n = 110 estimates), the median relative percent change in percent positivity was 25% (IQR: 13–44%, n = 49 estimates), and the median relative percent change in absolute number of rotavirus positive tests or rotavirus-specific International Classification of Diseases codes was 42% (IQR: 16–66%, n = 40 estimates).Conclusions These findings broadly suggest rotavirus vaccines provide some indirect protection. There is a need to standardize measurement of indirect rotavirus vaccine protection, particularly using consistent outcomes and metrics, and stratifying results by standardized age groups and years since vaccine introduction.